Pendekatan Joyful Learning untuk Meningkatkan Aktivitas Belajar Bangun Ruang pada Siswa Kelas V SD Negeri 6 Gedong Tataan Kabupaten Pesawaran TP 2019/2020 - Sutini Sutini (Program Studi PGSD, Jurusan Ilmu Pendidikan, STKIP PGRI Bandar Lampung, 2022)
The purpose of this research is to increase the activity and achievement of learning Mathematics in determining the volume of Building Space with a Joyful Learning approach, Class V students of SD Negeri 6 Gedong Tataan, Pesawaran Regency, Lampung Province 2019/2020. The research method uses a Classroom Action Research (Self Reflective Inquiry) design which is carried out in three research cycles. Through the stages of planning, implementation, observation and reflection. The results of the Cycle I study, the average learning outcomes were 62 with the Enough category, 63% Completed. Cycle II learning outcomes Average 78 in the Good category, Completed 81% Cycle III learning outcomes Average 87 in the Very Good category, Completed 96%. Learning activities in Cycle I 63%, Cycle II 81% and Cycle III 85%. Observer's observation about teacher's performance in learning is on average Good. Thus, the use of the Joyful Learning approach can increase the activity and achievement of learning mathematics in determining the volume of building spaces in Class V students of SD Negeri 6 Gedong Tataan Pesawaran 2019/2020.